Pengaruh Likuiditas dan Solvabilitas terhadap Profitabilitas (Studi pada Perusahaan Otomotif yang Terdaftar di Bursa Efek Indonesia - Anugrahni, Dwi Lira; Maithy, Sifera Patricia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The automotive industry in Indonesia has shown rapid development in recent years, driven by increasing public interest in motorized vehicles, stable economic growth and infrastructure progress. Automotive companies are required to innovate and increase competitiveness in an increasingly competitive market. A company's financial performance, especially profitability, is an important indicator in assessing effectiveness and efficiency in generating profits. A high profitability ratio reflects the company's ability to utilize resources optimally. Apart from that, liquidity and solvency ratios also affect company profitability. This research aims to analyze the influence of the Liquidity Ratio (Current Ratio) and Solvency Ratio (Debt to Equity Ratio) on the Profitability Ratio (Return of Assets) in six automotive subsector companies listed on the Indonesian Stock Exchange, namely Astra International Tbk, Astra Otoparts Tbk, Gajah Tunggal Tbk, Indomobil Sukses Internasional Tbk, Indospring Tbk, and Multi Prima Sejahtera Tbk, during the period 2020–2024. The research method used is quantitative, where research data is in the form of numbers and analysis uses statistics (Sugiyono, 2022). The data used is secondary data obtained from the company's annual financial reports. It is hoped that the research results can contribute to understanding the extent to which liquidity ratios and solvency ratios influence the profitability of automotive companies in Indonesia during the 2020–2024 period. It is hoped that these findings can be used as consideration for company management in making strategic decisions to improve the company's financial performance and competitiveness in the market.